Use of knowledge regarding LH receptors to improve superstimulatory treatments in cattle - Barros, Ciro M. [UNESP]; Ereno, Ronaldo Luiz [UNESP]; Simoes, Renato A. L. [UNESP]; Fernandes, Paulo [UNESP]; Buratini, Jose [UNESP]; Nogueira, Marcelo Fábio Gouveia [UNESP] (CSIRO Publishing, 2010)
Embryo transfer is a biotechnology that has been used worldwide to increase the production of offspring from female bovines. Treatments to induce multiple ovulations (superovulation) have evolved from superstimulatory protocols that depended upon detection of oestrus to treatments that synchronise follicle growth and ovulation, allowing for improved donor management and fixed-timed AI (FTAI). The protocols associated with FTAI facilitate animal handling and produce at least as many viably embryos as conventional treatment protocols that required detection of oestrus. Recent knowledge regarding LH receptors (LHR) and follicular development can be applied to improve embryo transfer protocols. In fact, improvements in the superstimulatory treatment called the 'P-36 protocol', which include hormones that stimulate LHR, indicate that adjustments related to LHR availability may increase bovine embryo yield compared with conventional protocols based on the detection of oestrus.
Keywords: bovine; embryo transfer; FSH